2022
DOI: 10.3389/fimmu.2022.918611
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of CD8+ T Cells for Optimized Vaccine Strategies Against Respiratory Viruses

Abstract: The primary goal of vaccines that protect against respiratory viruses appears to be the induction of neutralizing antibodies for a long period. Although this goal need not be changed, recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants have drawn strong attention to another arm of acquired immunity, CD8+ T cells, which are also called killer T cells. Recent evidence accumulated during the coronavirus disease 2019 (COVID-19) pandemic has revealed that even variants of SARS-CoV-2 that es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 123 publications
(126 reference statements)
0
4
0
Order By: Relevance
“…3 B and D), which was consistent with previous findings that inactivated virus and subunit vaccines are less efficient in inducing CD8 + T cells. 3 , 25 However, post BA.5 infection, virus-specific CD8 + T cell responses peaked at D14 with a higher proportion of Tnaïve and TEMRA phenotypes, showing a slower kinetics compared to CD4 + T cell response ( Fig. 6 ).…”
Section: Discussionmentioning
confidence: 96%
“…3 B and D), which was consistent with previous findings that inactivated virus and subunit vaccines are less efficient in inducing CD8 + T cells. 3 , 25 However, post BA.5 infection, virus-specific CD8 + T cell responses peaked at D14 with a higher proportion of Tnaïve and TEMRA phenotypes, showing a slower kinetics compared to CD4 + T cell response ( Fig. 6 ).…”
Section: Discussionmentioning
confidence: 96%
“… 14 , 36 , 37 Recent evidence accumulated during the SARS-CoV-2 pandemic has revealed that variants that escaped from nAbs that were induced by either natural infection or vaccination could not escape from CD8 T cell-mediated immunity. 38 As the vaccine-elicited antibody response wore off, most CD4 and CD8 T cells responses were preserved. 39 Accordingly, T cells have been credited with playing a key role in the sustained vaccine-mediated protection against hospitalization and death.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the role of antigen-specific T cells in protective immunity against SARS-CoV-2 infection, it is becoming increasingly clear that successful vaccines need to engage the cellular adaptive immune response. 70 , 71 , 72 Indeed, humoral immune responses may be less effective against SARS-CoV-2 variants. 73 , 74 Conversely, SARS-CoV-2-specific CD8 T cell responses, which target a broad range of epitopes, remain largely intact against variants.…”
Section: Discussionmentioning
confidence: 99%